2020
DOI: 10.1002/adom.202000239
|View full text |Cite
|
Sign up to set email alerts
|

A Bright and Stable Violet Carbon Dot Light‐Emitting Diode

Abstract: Violet light‐emitting diodes (LEDs) with emission at 400 nm are very important for solid‐state lighting, high‐density information storage, display technology, and biology medical treatment. Wide band‐gap semiconductors and/or the semiconductor quantum dots (QDs), typically based on heavy metals such as cadmium and lead, are promising candidates for the violet LEDs, but so far these have had external quantum efficiencies (EQEs) lower than 0.31% (luminance 147.6 cd cm−2; 410 nm). Herein, violet light‐emitting ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Fourier transform infrared (FTIR) spectrum of CDs is shown in Figure 1b, in which, a series of peaks located at 3455, 3245, 2921, 1632, 1381, and 1120 cm –1 were attributed to stretching vibration of O─H, stretching vibration of N─H, stretching vibration of C─H, stretching vibration of C═C/C═O/C═N, bending vibration of C─C/C─N and bending vibration of C─O, severally. [ 23,24 ] The FTIR spectra of CDs in the present and 5 years ago were drawn in Figure S2a–c, Supporting Information, suggesting the structural stability of CDs during 5‐year storage. X‐ray photoelectron spectroscopy (XPS) survey spectrum (Figure S1e, Supporting Information) confirmed that CDs only contain carbon, nitrogen, and oxygen elements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourier transform infrared (FTIR) spectrum of CDs is shown in Figure 1b, in which, a series of peaks located at 3455, 3245, 2921, 1632, 1381, and 1120 cm –1 were attributed to stretching vibration of O─H, stretching vibration of N─H, stretching vibration of C─H, stretching vibration of C═C/C═O/C═N, bending vibration of C─C/C─N and bending vibration of C─O, severally. [ 23,24 ] The FTIR spectra of CDs in the present and 5 years ago were drawn in Figure S2a–c, Supporting Information, suggesting the structural stability of CDs during 5‐year storage. X‐ray photoelectron spectroscopy (XPS) survey spectrum (Figure S1e, Supporting Information) confirmed that CDs only contain carbon, nitrogen, and oxygen elements.…”
Section: Resultsmentioning
confidence: 99%
“…And the emissive peak located at 444 nm when the temperature was frozen to 5 K. The position of emission peak red‐shifted by 3 nm for all the process of temperature increment from 5 to 293 K. It could be explained by enhancing the possibility of carrier coupling because of the increment of temperature with the improvement of the distortions and structural vibrations. [ 23,29 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexural vibration of C-C/C-N and C-O are observed at 1382 and 1238 cm -1 . [31][32]40] Ultraviolet and visible spectrophotometry (UV-vis) is usually used to research into the optical absorption properties of materials. In the Figure 1c, the strong absorption peak situated at 204 nm indicates that π-π* transition of conjugated aromatic C=C bond.…”
Section: Structural Characterizations Of Carbon Dotsmentioning
confidence: 99%
“…Also, CDs have opened up an avenue in community of light‐emitting diodes (LEDs) resulting from their inherent optical advantages, such as emission wavelength tunability, high photoluminescence quantum yield (PLQY), good solubility in different solvents and low photobleaching [25–34] . Up to now, by using diverse synthetic methods and various precursors, CDs have been fabricated with photoluminescence (PL) emission from red to violet [35] . Very recently, the development of this field is rapid, the PLQY of some CDs is up to 90 %, and the full width at half maxima (FWHM) of their PL spectrum are narrow to about 20 nm, [36–39] which are basically close to the requirements of display devices.…”
Section: Introductionmentioning
confidence: 99%